Effectiveness of Health Education Videos on Knowledge of Preventive Care for Foot Wounds in Diabetes Patients: A Systematic Literature Review - Andi Muh. Zulfikar; Fitrah (Jurnal Kesehatan STIKes Sumber Waras, 2025)
Based on data from the International Diabetes Federation (IDF), in 2024, 106.9 million adults aged 20-79 years in Southeast Asia will develop diabetes. This number is estimated to increase by 73%, reaching 185 million people by 2050. This increase in cases continues to occur due to problems in producing insulin so that cells cannot receive glucose for metabolism. The purpose of this study was to determine the effectiveness of health education videos on knowledge of foot wound prevention care in diabetic patients. The method in this study used a Systematic Literature Review, searching for data or information sources through Google Scholar, then conducting selection through quality assessment with inclusion and exclusion criteria. The results of the study showed that the initial level of knowledge of diabetes patients, especially regarding foot care and wound prevention, was in the category of poor to very poor before educational interventions were given. After education, there was a significant increase in the level of knowledge after providing education using video/digital media. The conclusions collectively confirm that educational videos or digital/audiovisual media are highly effective and relevant intervention methods for increasing patient knowledge and behavioral intentions for foot ulcer prevention. This increased understanding is key to fostering patient awareness and self-care skills, which ultimately reduces the risk of serious complications such as diabetic foot ulcers. Keywords : Foot Wounds, Diabetes, Education, Video.